Determinan Perilaku Beli Produk Bahan Makanan Berlogo Halal - sumadi sumadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2022)
This study aims to identify the impact of halal logo toward halal food, attitudes, subjective norms and attitudes on buying interest and buying behavior for groceries with halal logo.Empirical research was conducted in this study by consumer survey. The population are Muslim in Indonesia with non-probability sampling and the target of those who are selected and voluntarily. This study used 256 sampless. Data collected using questionnaires that were distributed directly to target respondents through direct face-to-face media and through google form. The data were analyzed using the Structural Equation Modeling (SEM) version of the AMOS statistical analysis tool. The results of the study concluded that there is a positive and significant impact between the halal food logo on attitudes towards halal food objects. Subjective attitudes and norms have a positive and significant influence on buying interest and buying behavior for halal food. The independent variables of the halal logo for halal food and subjective norms can both be used as factors (determinants) to predict the behavior of buying halal food.